Effectiveness of Specialized Cervical Collars in Reducing Pain Associated with Cervical Syndrome among Computer Workers - zubaidi, Alfan; Suprayogi, Dody; akbar, Muh Syaiful (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Cervical syndrome is a prevalent musculoskeletal disorder among computer workers, primarily caused by prolonged static postures and poor ergonomic practices. It leads to chronic neck pain, muscle stiffness, and reduced work productivity. Addressing this issue, ergonomic interventions such as specialized cervical collars can help mitigate discomfort and prevent further complications. This study aims to evaluate the effectiveness of a customized cervical collar in reducing neck pain among computer workers in Karanganyar Regency. Specifically, it investigates whether a specially designed collar provides more effective pain relief compared to commercially available collars. This study contributes to occupational health by proposing an ergonomic intervention that may improve the well-being of computer workers. It highlights the potential benefits of personalized cervical support, which may influence workplace ergonomic policies and musculoskeletal disorder prevention strategies. A pre- and post-test experimental design was used to assess pain reduction using the Visual Analog Scale (VAS). The study involved 80 computer workers diagnosed with cervical syndrome. Participants underwent a baseline pain assessment using the VAS before the intervention. The intervention group used a customized cervical collar, while the control group used a standard commercial collar. Pain levels were reassessed after a specified intervention period. Data were analyzed using paired t-tests to evaluate the significance of pain reduction, with additional correlation analysis conducted to examine relationships between pre- and post-intervention scores. The findings revealed a significant reduction in neck pain within the intervention group. The mean pain score decreased from 4.29 to 2.25 (p < 0.001), with a large effect size (Cohen’s d = 2.401). Correlation analysis showed a meaningful relationship (r = 0.292, p = 0.009) between pre- and post-intervention pain levels, confirming the effectiveness of the customized cervical collar. This study demonstrates that a customized cervical collar is highly effective in reducing neck pain among computer workers. These results support its use as an ergonomic intervention for preventing work-related musculoskeletal disorders. Future research should explore long-term benefits and compliance rates in various occupational settings.